2018
DOI: 10.1111/jcmm.14018
|View full text |Cite
|
Sign up to set email alerts
|

Two human MARs effectively increase transgene expression in transfected CHO cells

Abstract: Matrix attachment regions (MARs) can enhance the expression level of transgene in Chinese hamster ovaries (CHO) cell expression system. However, improvements in function and analyses of the mechanism remains unclear. In this study, we screened two new and more functional MAR elements from the human genome DNA. The human MAR‐3 and MAR‐7 element were cloned and inserted downstream of the polyA site in a eukaryotic vector. The constructs were transfected into CHO cells, and screened under G418 to produce the stab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 12 publications
2
12
0
Order By: Relevance
“…We previously screened a series of MAR sequences and designed synthetic MARs based on the characteristics of MAR sequences to improve the levels and stability of transgenic expression in CHO cells . We also analyzed the molecular characteristics of MAR elements that are requisite in improving transgenic expression in CHO cells .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously screened a series of MAR sequences and designed synthetic MARs based on the characteristics of MAR sequences to improve the levels and stability of transgenic expression in CHO cells . We also analyzed the molecular characteristics of MAR elements that are requisite in improving transgenic expression in CHO cells .…”
Section: Discussionmentioning
confidence: 99%
“…We previously screened a series of MAR sequences and designed synthetic MARs based on the characteristics of MAR sequences to improve the levels and stability of transgenic expression in CHO cells. 14,19,25,26 We also analyzed the molecular characteristics of MAR elements that are requisite in improving transgenic expression in CHO cells. 21 Bioinformatic analysis showed that the elements encode a MAR-like motif and some transcription factor binding sites such as CEBP, CTCF, GSH, and SATB1binding motifs may be conducive to the MAR-mediated augmentation of transgenic expression.…”
Section: Discussionmentioning
confidence: 99%
“…An appropriate combination of expression vector elements can improve the expression of recombinant proteins, overcome gene silencing, and increase the stability of transgene expression. At present, there have been reports on matrix attachment regions (MARs) ( Gao et al, 2019 ; Jia et al, 2019 ; Li et al, 2019 ), ubiquitous chromatin opening elements ( Saunders et al, 2015 ), cis-acting factors ( Wang et al, 2018 ), stabilizing Anti Repressor elements ( Hoeksema et al, 2011 ), introns ( Osabe et al, 2017 ), internal ribosome entry sites (IRES) ( Chai et al, 2018 ), exons ( Lu et al, 2017 ) and promoters ( Wang et al, 2017 ; Yi et al, 2020 ), and found that these elements can improve the expression of recombinant proteins to some extent.…”
Section: Mammalian Cells and Expression Vectorsmentioning
confidence: 99%
“…Interestingly, the same group reported that for mouse liver 65 or human mesenchymal stem cells, 52 both the vector and the transgene should be CpG free, whereas in mouse skeletal muscle, 65 removing the CpG motifs from the vector alone was sufficient to maintaining expression for about 100 days relative to control vector. Noticeably, other vectors with similar dual S/MAR regions (IFNβ S/MAR and an immunoglobulin S/MAR 66 or short chimeric MARs 67 ) promote higher colony formation, transgene expression levels, and maintenance in CHO cells relative to one S/MAR, suggesting that more than one S/MAR may augment the vector's activity and function further.…”
Section: Episomal Vectors Devoid Of Harmful Dna Sequencesmentioning
confidence: 99%